DEPRESSION AND LONELINESS IN MID- AND LATER LIFE - Zhao, F (Innov Aging, 2018)
Existing studies have shown a close relationship between depression and loneliness among older adults, but it has been less clear about the causal direction of this relationship and how the levels of depression and loneliness change over a longer period in mid- and later life. This study investigated the causal influences between depression and loneliness across three time points (2008, 2012, and 2016) using cross-lagged panel (CLP) analysis and examined the trajectories of depression and loneliness in the same time period using latent growth curve (LGC) analysis. Respondents were 2695 adults (aged 51 to 91) from three waves of Health and Retirement Study. The results of CLP model indicated that there was a bidirectional relationship between depression and loneliness, but the effects of loneliness at earlier time points on later depression were larger than that of previous depression on later loneliness. The LGC models showed significant positive associations between the initial levels of depression and loneliness and between the rates of change of these two variables. Significant individual differences were also found in the initial levels and the rates of change for both depression and loneliness. The results further found that age negatively associated with the initial levels of both depression and loneliness but positively related to the rate of change of these two variables. The study highlighted the reciprocal relationship between depression and loneliness and showed the effect of age on the initial levels and rates of change of these two variables.